Peculiarities Of Lifestyle And Mental Health Of Students On Distant Education During Novel Coronavirus Infection Endemic (Covid-19) - Ismail A. Miziev, Аksana M. Kаrdаngushevа, Liliya V. Elgarova, Ivanov Anatoly Betalovich, Antonina F. Budnik, Tauzhan K. Agnokova, Zukhra A. Gelyakhova (Drugs and Cell Therapies in Hematology, 2021)
Aim: to study the peculiarities of life activities and mental health of students at the Kabardino-Balkarian State University named after H.M. Berbekov that are on distant education during novel coronavirus infection pandemic (COVID-19). Materials and Methods. From January 27th to February 8th 2021, the authors conducted an online survey via an internet platform Goodle Forms using a special digitally converted epidemiological questionnaire. The survey included 256 students (222 women ad 34 men) aged 16-29 years old. Results. After a shift of students on distant education, the time of preparation to the studies increased (42.9%) as well as the rate of smoking (all smokers), consumption of vegetables (36.7%) and fruits (43.8%), and duration of sleep (60.9%). A decrease in physical activities (62.9%) and rate of meals at cafes and restaurants (100%) was observed. In 19.1% of students, a high level of state anxiety was observed. In 37.5% of students, a high level of trait anxiety was revealed. Anxiety was reported by 50% of students and depression – by 25% of students. Conclusion. The authors revealed unfavorable (increase in the time of preparation and number of cigarettes per day, decrease in the physical activity, high rate of anxiety levels, anxiety, and depression) and favorable (increase in the time of sleeping, decrease in the rate of meals at cafes and restaurants, and no changes in the rate of purchase or order of ready-made meals) changes in the period of distant education. The obtained results could be used for the development of programs that could protect the health of students on distant education who use digital technologies.